Innovative Face Recognition System for Efficient Access Management in Academic Institution - Douglas Rakasiwi Nugroho; Rico Aurelio Gunadi Sastra (AIBPM Publisher, 2024)
This paper introduces a proof of concept for an innovative device aimed at enhancing administrative efficiency in academic environments through advanced facial recognition technology. Designed to a large, portrait-oriented display and an integrated camera, the device is intended to be installed at various strategic locations across the campus, facilitating streamlined access to information. By replacing traditional login methods, it enables students and faculty members to access essential information quickly and effortlessly after a brief identity verification process. This efficient approach not only minimizes time spent on routine administrative tasks but also ensures a seamless user experience. In this paper, we aim to demonstrate that this concept can be realized by combining several elements, which will be detailed in the content. Additionally, it highlights the role this technology plays in advancing campus infrastructure, fostering a more efficient, and technologically equipped academic environment. Through this initiative, the paper contributes to the broader conversation on modernizing educational institutions by integrating facial recognition into everyday campus interactions